Penerapan Technology-Enhanced Learning dalam Pengembangan Pendidikan Agama Islam pada Anak Usia Dini - Sulastri, Sulastri; Ismail, Ismail (Absorbent Mind, 2025)
The development of digital technology has brought significant changes in the world of education, including Islamic education. This study aims to determine the use of technology in developing Islamic religious education for early childhood at PAUD Among Putro Melati Kasihan. The research method used in this study is descriptive qualitative, which aims to explore the application of Technology-Enhanced Learning (TEL) in Islamic religious education at PAUD. The results of the study indicate that the use of technology in learning Islamic Religious Education (PAI) at PAUD provides various benefits, such as increasing children's interest and understanding. Based on Richard E. Mayer's theory of cognitive multimedia, the use of media such as images and videos can help reduce cognitive load and facilitate the learning process. In addition, the application of Vygotsky's theory of social interaction is also relevant, where platforms such as Google Classroom and Zoom increase the dynamics of interaction. The principal and teachers at PAUD Among Putro Melati utilize applications, animated videos, and interactive stories to convey religious values ​​in a fun way and enrich the learning experience. Despite the challenges of technology addiction, lack of social interaction, and limited access to devices, the use of technology in Islamic religious education has been shown to have a positive impact on children's religious understanding and character development, as long as it is accompanied by proper supervision.